(untitled) (LINGUISTICA, 2015)
The study deals with the use of connotative meaning especially in DarwisTereLiye™s quotes. In this study the researcher focuses on the three main types of connotative meaning namely positive connotative, negative connotative and neutral connotative. The data that support this study are obtained by applying descriptive qualitative method by selecting and then analyzing some quotes of DarwisTereLiye on facebook. The findings show that there are three types of connotative meaning in DarwisTereLiye™s quotes. There are positive connotative, negative connotative and neutral connotative. Positive connotative as the dominant type that found in this research.